Why has China grown so fast for so long? - Malik, Khalid, 1952- (New Delhi ; Oxford : Oxford University Press, 2012)
Based on the author's experience of living and working in China, this book uses the lens of development economics to identify the key social and economic forces that can help explain China's stellar growth success.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Economic development -- China; China -- Economic conditions -- 1976-2000.; China -- Economic conditions -- 2000-